2001
DOI: 10.1128/iai.69.5.2888-2893.2001
|View full text |Cite
|
Sign up to set email alerts
|

Search for Correlates of Protective Immunity Conferred by Anthrax Vaccine

Abstract: Vaccination by anthrax protective antigen (PA)-based vaccines requires multiple immunization, underlying the need to develop more efficacious vaccines or alternative vaccination regimens. In spite of the vast use of PA-based vaccines, the definition of a marker for protective immunity is still lacking. Here we describe studies designed to help define such markers. To this end we have immunized guinea pigs by different methods and monitored the immune response and the corresponding extent of protection against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
181
4
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(197 citation statements)
references
References 41 publications
11
181
4
1
Order By: Relevance
“…We initially hypothesized that a potency assay like the TNA assay would provide a means of determining the functional antibody response to PA in neutralizing the cytotoxic effects of LeTx. Our findings in mice contrast with those of Reuveny et al [19] who reported that the TNA assay may be useful as a surrogate marker for protection in guinea pigs. Alternatively, a competitive ELISA using monoclonal antibodies that define functional epitopes of PA may be informative [27].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We initially hypothesized that a potency assay like the TNA assay would provide a means of determining the functional antibody response to PA in neutralizing the cytotoxic effects of LeTx. Our findings in mice contrast with those of Reuveny et al [19] who reported that the TNA assay may be useful as a surrogate marker for protection in guinea pigs. Alternatively, a competitive ELISA using monoclonal antibodies that define functional epitopes of PA may be informative [27].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies demonstrated that a quantitative anti-PA IgG ELISA and toxin neutralizing antibody (TNA) assay served as immunological correlates to immunity in New Zealand white rabbits previously inoculated with AVA [15]. Passive protection studies with anti-PA antibodies demonstrated the significant role that antibodies play in protecting laboratory animals against infection [16][17][18][19]. Current studies have focused on development of the next-generation anthrax vaccine based upon recombinant PA (rPA) administered with Alhydrogel or alum.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of PA in vaccines to protect against anthrax intoxication or infection [10][11][12][13]. The importance of anti-PA serum also has been shown in the identification of in vitro correlates of immunity [14][15][16][17] and in passive antibody studies [18][19][20]. This report evaluates the role of the aluminum hydroxide gel adjuvant and the excepient formaldehyde in the formulation of rPA vaccines in the rabbit model using in vitro surrogate markers (the quantitative anti-rPA IgG ELISA and toxin neutralizing antibody (TNA) assay) and efficacy studies.…”
Section: Subject Termsmentioning
confidence: 99%
“…We did not observe a decrease in the TNA assay ED 50 titers in the rabbit animal model at the highest concentration of aluminum tested (500 g). Both the anti-PA ELISA titer and toxin neutralizing antibody titers have been identified as serological correlates of immunity in rabbits and guinea pigs [13][14][15][16][17]25] and are thus important measurements in developing effective vaccine strategies. Various formulations have been tested in preparing anthrax vaccines based upon rPA for its ability to elicit optimal immunological responses.…”
Section: Effect Of Formaldehyde On Serological Response and Protectionmentioning
confidence: 99%
“…In addition, it has previously been shown that immunization with domain 4 generates antibodies that are sufficient to provide protection against spore and toxin challenge in mice (8,26). Also, there are other neutralizing epitopes in domains 1 to 3 (12,34). In this study, we evaluated the antibody response and the titer that correlated with toxin neutralization in four strains of mice.…”
mentioning
confidence: 98%